Reliability physics and engineering time-to-failure modeling - McPherson, J. W. (Springer, 2019)
This third edition textbook provides the basics of reliability physics and engineering that are needed by electrical engineers, mechanical engineers, civil engineers, biomedical engineers, materials scientists, and applied physicists to help them to build better devices/products.